Competitive Advantages of Sharia Banks: Role of Ihsan Behavior and Digital Marketing in New Normal - Mohamad Sodikin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
Covid pandemic 19 had an impact on all aspects, one of which was related to Islamic banking. This article aims to discuss the role of Ihsan's behaviour as a foundation in building relationships with customers, building brand image through communication with the characteristics of Islamic values, and how organizations provide support so that the development of digital marketing communication runs effectively. The method uses a qualitative approach, with secondary data sources. Data analysis uses descriptive analysis approach. The results of the study show that the new pattern of life called the new normal as a result of the co-19 pandemic has affected various sectors of social, economic, and even religious life. Islamic banks, as part of institutions that have an important role must be able to adapt and have a strategy to establish excellent communication and services with their customers. The business foundation, with the foundation of Ihsan values, with communication strategies through digital media, is expected to be able to increase the advantages of Islamic banks.